Zeb1 and twist are more commonly expressed in metastatic than primary lung tumours and show inverse associations with claudins. Issue 2 (2nd December 2010) - Merikallio, Heta; Kaarteenaho, Riitta; Pääkkö, Paavo; Lehtonen, Siri; Hirvikoski, Pasi; Mäkitaro, Riitta; Harju, Terttu; Soini, Ylermi
Abstract : Background: Zeb1 and twist regulate expression of genes which take part in epitheliomesenchymal transition (EMT). Claudins are tight junctional proteins regulating polarity and paracellular permeability of epithelial cells. Aims and methods: To study Zeb1 and twist in 289 primary and 54 metastatic lung tumours and their relation to expression of claudins 1–5 and 7 by immunohistochemistry. Results: Metastatic tumours showed a significantly lower expression of zeb1 and twist (33.0% and 38.0% vs 5.0% and 14.5%, p<0.001 for both) and they also had a significantly lower expression of claudin 1 (p<0.001), claudin 4 (p<0.001), claudin 5 (p=0.001) and claudin 7 (p<0.001) than did primary tumours. Primary lung tumours showed a strong inverse association between zeb1 and claudin 1 (p=0.024) and claudin 2 (p=0.003). For twist an inverse association was found with claudin 5 (p=0.007). In metastatic tumours zeb1 was inversely associated with claudin 7 (p=0.050) and twist with claudin 5 (p=0.025). Overexpression of claudin 5 was associated with decreased survival (p=0.017). For zeb1 or twist, no association with survival was observed in primary or metastatic tumours. Conclusions: According to protein expression, involvement of zeb1 and twist in EMT in primary lung tumours is relatively infrequent. Carcinomas metastatic to the lung showed a significantly higher expression of these transcriptional factors than primary lung tumours, indicating their probable importance in the metastatic process. Zeb1 and twist were inversely associated with several claudins, indicating a role in their down-regulation.